Coexistence of Ovarian Mucinous Adeno Carcinoma and Benign Brenner Tumor: A Case Report - Özlem Seçilmiş Kerimoğlu; Pınar Karabağlı; Aybike Tazegül; Çetin Çelik (Medical Network, 2011)
Mucinous ovarian tumors are known to coexist sometimes with Brenner tumors; however, in many of the cases in the literature, mucinous cystadenomas are seen to have been analyzed. In this case report, we aimed to present a case who was operated on in our clinic, and who was diagnosed as mucinous adenocarcinoma and coexisting benign Brenner tumor. In this case report, we aimed to present the outcomes of a 57-year-old patient with a history of 6 pregnancies, 4 living children and 2 abortuses, who presented to our hospital with the complaint of abnormal vaginal bleeding, and in whom a cystic lesion was detected in the left ovary on physical and radiological examinations. The Ca 125 level was normal. The patient underwent the operation with the pre-diagnosis of postmenopausal ovarian mass in which total abdominal hysterectomy, bilateral salpingooophorectomy, total omentectomy and bilateral pelvic-para-aortic lymph node dissection were performed. The pathology result was reported as left ovarian mucinous adenocarcinoma and benign Brenner tumor. The rate of Brenner tumor accompanying mucinous cystadenoma has been reported as 1.3% and the rate of mucinous adenocarcinoma accompanying Brenner tumor has been reported as 9%. However, its coexistence with mucinous adenocarcinoma is rare as in our case. In case of presence of the diagnosis of mucinous cystadenocarcinoma or cystadenoma, assessment of the ipsilateral or contralateral ovarian cysts in terms of presence of Brenner tumor and further molecular cytogenetic analysis of the detected cases can shed light on the development histogenetics of these tumors.